2015
DOI: 10.1586/14737175.2015.1001748
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between oxidative stress-related gene polymorphisms and chronic migraine in an Italian population

Abstract: Migraine patients present increased risks of vascular diseases such as high blood pressure, insulin resistance, metabolic syndrome, stroke and coronary heart disease. Oxidative stress (OS) is increasingly being studied in relation to the pathophysiology of migraine, stimulated by the described association with the most frequent migraine comorbidities. Because many of the gene-encoded players of the OS balance are characterized by functional polymorphisms, it is supposed that the individual genomic profile coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…Oxidative stress is a subject increasing in popularity regarding its relation to the pathophysiology of migraine. However, a study that investigated 10 polymorphisms in 8 oxidative stress-related genes in a small population of CM patients did not detect a relationship with CM [51]. However, as migraine is considered a complex disease with multifactorial inheritance, Genome-Wide Association Study (GWAS) seems a more appropriate approach to study migraine genetic background.…”
Section: Genetics and Epigeneticsmentioning
confidence: 99%
“…Oxidative stress is a subject increasing in popularity regarding its relation to the pathophysiology of migraine. However, a study that investigated 10 polymorphisms in 8 oxidative stress-related genes in a small population of CM patients did not detect a relationship with CM [51]. However, as migraine is considered a complex disease with multifactorial inheritance, Genome-Wide Association Study (GWAS) seems a more appropriate approach to study migraine genetic background.…”
Section: Genetics and Epigeneticsmentioning
confidence: 99%
“…However, so far studies have not shown association between gene polymorphisms associated with oxidative stress and the occurrence of CM. On the other hand, repetitive painful stimuli on the trigeminal nerve cause activation of the pain modulating descending system in several portions, including the periaqueductal gray matter, showing that during migraine attacks, the neurons of this region show increased activity, which may lead to oxidative stress and finally dysfunction of nociceptive modulation by such system [33,[41][42][43].…”
Section: Pathophysiologymentioning
confidence: 99%
“…The search strategy on PubMed and Web of Knowledge identified a total of 128 studies, of which 16 were duplicates. After the removal of 95 hits not fulfilling the inclusion criteria, 17 studies were finally included in the qualitative review of gene association studies focusing on MOH (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). The main characteristics of the identified studies are summarized in Table 1 between 2006 and 2015 by five research groups, four of which were located in Italy -including our group -and one in Japan, with sample sizes of MOH patients ranging from 22 to 227.…”
Section: Characteristics Of Identified Studiesmentioning
confidence: 99%
“…The main characteristics of the identified studies are summarized in Table 1 between 2006 and 2015 by five research groups, four of which were located in Italy -including our group -and one in Japan, with sample sizes of MOH patients ranging from 22 to 227. Twelve studies had a case-control design (22,(25)(26)(27)(28)(29)(31)(32)(33)(34)36,37), while the remaining five were case-only studies (23,24,30,35,38). Thirteen studies were conducted on MOH patients with Caucasian ancestry (22)(23)(24)(25)(26)(27)29,30,(34)(35)(36)(37)(38), while four studies recruited MOH patients with Asian ethnicity (28,(31)(32)(33).…”
Section: Characteristics Of Identified Studiesmentioning
confidence: 99%
See 1 more Smart Citation